2020
DOI: 10.1002/acn3.51194
|View full text |Cite
|
Sign up to set email alerts
|

Promoting identification of amyotrophic lateral sclerosis based on label‐free plasma spectroscopy

Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is an adult-onset fatal neurodegenerative disease which lacks identified biological markers. A label-free plasma surface-enhanced Raman spectroscopy (SERS) method was developed to explore a simple and noninvasive test for ALS. Methods: ALS patients were enrolled serially and plasma samples were collected at the time of diagnosis prior to the start of ALS treatment. SERS spectra were recorded using a Renishaw micro-Raman system. Results: To exclude the interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Whether phenylalanine has a mediation effect between ALS and MS needs to be further studied. In prior literature, tryptophan and competing neutral amino acid levels were found to be diminished in the plasma of patients with neurodegenerative diseases, the greatest decrease being of tryptophan (Monaco et al, 1979;Zhang et al, 2020). Evidence was also shown that higher serum phenylalanine concentrations related to immune activation are detectable in a subgroup of AD patients (Wissmann et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Whether phenylalanine has a mediation effect between ALS and MS needs to be further studied. In prior literature, tryptophan and competing neutral amino acid levels were found to be diminished in the plasma of patients with neurodegenerative diseases, the greatest decrease being of tryptophan (Monaco et al, 1979;Zhang et al, 2020). Evidence was also shown that higher serum phenylalanine concentrations related to immune activation are detectable in a subgroup of AD patients (Wissmann et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Zhang et al used SERS with PCA and CRT ML algorithm to distinguish Raman spectral data between 182 ALS and 60 healthy patient plasma samples that were mixed with colloidal Ag NPs. 83 The authors identified adenine and coenzyme A (722 cm −1 ), thymine and uracil (739 cm −1 ), and the ratio of tyrosine peak at 635 cm −1 to the aforementioned peaks as the most significant in distinguishing the two cohorts. The SERS bands for nucleic acids were higher in ALS patients confirming well-established literature evidence of altered DNA/RNA metabolism that contribute to genetic mutations in ALS.…”
Section: Chemicalmentioning
confidence: 99%
“…Raman spectral data can then be combined with ML algorithms and multivariate analysis to enable accurate diagnostics of disease progression and discrimination between disease subtypes. By probing these metabolites, RS has characterized tissue, cells, and biofluids , including tears, urine, saliva, serum, and plasma. However, a limitation of spontaneous RS is the time required for a reasonable SNR, which limits both the ability for subcellular imaging and to monitor processes in real time. Both of these characteristics are necessary to understand the mechanistic pathway of metabolic changes.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the indices of persistent sodium current and fast potassium conductance were significantly associated with survival in ALS patients, and moreover, that a longer strength-duration time constant (SDTC), which indicates an increased persistent sodium current in motor axons, was a strong predictor for ALS survival 7 . Although some metabolites in plasma have been suggested as potential diagnostic/surrogate biomarkers for ALS 8 , no plasma biomarkers closely linked to motor nerve axonal excitability indices specific for ALS have been reported.…”
Section: Introductionmentioning
confidence: 99%